ADDRESS TERMS ANALYSIS IN THE “GRIDIRON GANG” MOVIE: THE TYPES AND THE FUNCTIONS - Aditya Pratama Ramadhan; Ambalegin, Ambalegin (Asosiasi Ide Bahasa Kepri, 2023)
The aim of this qualitative research was to reveal the types and functions of address terms in the Gridiron Gang movie. It applied the theories of Chaika (1982) and Wardhaugh (2014). observation method and non-participatory technique were employed to collect the data. Sociolinguistic approach was used for this study. Referential identity method and equalizing technique were then used to analyze the data. The result of this study is reported in descriptively and narratively. It was found all types and functions of address; Special nickname, First name, title only, kinship term, last name, pet name, and title plus last name. Special nickname was the most prevalent kind. Moreover, all three functions of address terms were discovered. The function of address terms most often used is to distinguish between stranger and power. Special nickname was used to demonstrate different power and authority in a prison or on a sports field. Additionally, there were three unique data. The uniqueness between these three data and others were that the function of the type of address term different from which is proposed by Wardhaugh and Chaika’s theory.